Examining car guarding as a livelihood in the informal sector. (September 2017) - Foster, John; Chasomeris, Mihalis
Car guarding is a distinctly South African informal sector employment activity. A car guard offers to guard vehicles in a public or private parking area for a donation. Car guarding enables an unemployed person to earn some income. The purpose of this study is to examine car guarding as a livelihood in the informal sector. This study interviews 30 car guards at six different locations in Durban, South Africa. It examines their demographic characteristics, income, education and skills, risks and challenges faced, and the opinion of car guards regarding their livelihood. The average car guard worked six days per week and an average of nine hours per day. The average income per hour ranged from ZAR4.64 to ZAR30. Average daily incomes ranged from ZAR50 to ZAR350. Car guarding is a high risk activity that includes health risks, and risks of verbal abuse and violence.